Changes in Quality of Life in the First 5 Years of Disease in a Multicenter Cohort of Patients With Systemic Lupus Erythematosus. Issue 9 (September 2014) - Urowitz, M.; Gladman, D. D.; Ibañez, D.; Sanchez‐Guerrero, J.; Bae, S. C.; Gordon, C.; Fortin, P. R.; Clarke, A.; Bernatsky, S.; Hanly, J. G.; Wallace, D. J.; Isenberg, D.; et al.
<x xml:space="preserve">Abstract</x> Objective The Medical Outcomes Study Short Form 36 (SF‐36) is recommended to assess quality of life (QOL) in systemic lupus erythematosus (SLE). The aim of the current study was to assess QOL over time in the first 5 years of a multicenter inception cohort of patients with SLE. Methods An inception SLE cohort was assembled according to a standardized protocol between 2000 and 2012. In addition to clinical and laboratory assessments, patients completed the SF‐36 at yearly intervals. Only patients who had ≥5 completed QOL questionnaires were included in these analyses. Generalized estimating equation models were run separately for each of the 8 subscales and for the physical and mental component summary scores, adjusting for repeated measures by patients. Results A total of 495 patients were included. The mean ± SD disease duration at the first visit was 5.3 ± 4.1 months. The mean ± SD age at enrollment was 35.8 ± 13.2 years. All 8 subscales and the 2 summary scores showed improvement in the first 2 years from enrollment. Between years 2 and 5, none of the subscales or summary scores showed any change. Minimum clinically important improvement was achieved by 35–56% of the patients and was influenced by demographic and disease factors. Conclusion Unlike late‐stage lupus, where QOL is stable over time, in patients with early disease, all subscales improve in early followup up to 2 years. Therefore, the SF‐36 may be a sensitive outcome measure in early disease in patients with SLE.